Regulation of peripheral expression of glucagon‐like peptide 1 receptors in a rat streptozotocin‐model of sporadic Alzheimer's disease. (1st February 2022) - Homolak, Jan; Knezovic, Ana; Perhoc, Ana Babic; Barilar, Jelena Osmanovic; Salkovic‐Petrisic, Melita
Abstract: Background: Our previous research indicated incretin dysregulation in a rat model of sporadic Alzheimer's disease (sAD) induced by intracerebroventricular streptozotocin (STZ‐icv) and improvement of cognitive decline following oral galactose‐induced potentiation of endogenous glucagon‐like peptide 1 (GLP‐1). This study explored peripheral GLP‐1 receptors (GLP‐1R) in STZ‐icv rats following the acute inhibition of cerebral GLP‐1 signaling and additional acute oral galactose administration. Method: 1 month following STZ‐icv treatment, male Wistar rats were acutely icv‐treated with GLP‐1R antagonist Exendin9‐39 (85ug/kg; /EXE‐icv/) (Experiment I), and 1 hour after EXE‐icv additionally with D‐galactose (200mg/kg, single oral dose) (Experiment II). Total/active GLP‐1 levels were analyzed in plasma and cerebrospinal fluid (CSF) by ELISA. GLP‐1R distribution in paraffin embedded duodenal/mesenteric adipose tissue was examined using catalyzed deposition of fluorescent reporters, and analyzed by hierarchical mixed‐effect modelling. Result: Baseline plasma level of active GLP‐1 was increased in STZ‐icv group (vs controls) while EXE‐icv treatment decreased it in the STZ‐icv and increased in the control group. In CSF, EXE‐icv induced a trend of GLP‐1 increment both in STZ‐icv and control group. Following acute oral galactose treatment, the same trend was observed in plasma of controls, but EXE‐icv didn't exhibit a reduction in STZ‐icv animals, and CSF level remained unchanged in both. The GLP‐1R expression in periduodenal mesenteric adipose tissue of STZ‐icv rats was increased following EXE‐icv but decreased following additional acute oral galactose treatment. Acute galactose treatment unmasked the effect of EXE‐icv on duodenal regulation of GLP‐1 as lacteal GLP‐1R signal was decreased both in STZ‐icv and control group following EXE‐icv. Conclusion: Our preliminary results support the existence of dysregulated GLP‐1 brain‐periphery axis in the STZ‐icv rat model of sAD, and additionally indicate that incretin dysregulation is localized both in the brain and the peripheral tissues of STZ‐icv rats, and that brain GLP‐1 seems to be involved in regulation of the peripheral GLP‐1R distribution. Funded by the Croatian Science Foundation (IP‐2018‐01‐8938). Co‐financed by the Scientific Centre of Excellence for Basic, Clinical and Translational Neuroscience (project "Experimental and clinical research of hypoxic‐ischemic damage in perinatal and adult brain"; GA KK01.1.1.01.0007 funded by the European Union through the European Regional Development Fund).